Rumen Microbiome Composition Is Altered in Sheep Divergent in Feed Efficiency - Steven McLoughlin; Steven McLoughlin; Charles Spillane; Noel Claffey; Paul E. Smith; Tommy O’Rourke; Michael G. Diskin; Sinéad M. Waters; Sinéad M. Waters (Frontiers in Microbiology, 2020)
Rumen microbiome composition and functionality is linked to animal feed efficiency, particularly for bovine ruminants. To investigate this in sheep, we compared rumen bacterial and archaeal populations (and predicted metabolic processes) of sheep divergent for the feed efficiency trait feed conversion ratio (FCR). In our study 50 Texel cross Scottish Blackface (TXSB) ram lambs were selected from an original cohort of 200 lambs. From these, 26 were further selected for experimentation based on their extreme FCR (High Feed Efficiency, HFE = 13; Low Feed Efficiency, LFE = 13). Animals were fed a 95% concentrate diet ad libitum over 36 days. 16S rRNA amplicon sequencing was used to investigate the rumen bacterial and archaeal communities in the liquid and solid rumen fractions of sheep divergent for FCR. Weighted UniFrac distances separated HFE and LFE archaea communities from the liquid rumen fraction (Permanova, P < 0.05), with greater variation observed for the LFE cohort (Permdisp, P < 0.05). LFE animals exhibited greater Shannon and Simpson diversity indices, which was significant for the liquid rumen fraction (P < 0.05). Methanobrevibacter olleyae (in liquid and solid fractions) and Methanobrevibacter millerae (liquid fraction) were differentially abundant, and increased in the LFE cohort (P.adj < 0.05), while Methanobrevibacter wolinii (liquid fraction) was increased in the HFE cohort (P.adj < 0.05). This suggests that methanogenic archaea may be responsible for a potential loss of energy for the LFE cohort. Bacterial community composition (Permanova, P > 0.1) and diversity (P > 0.1) was not affected by the FCR phenotype. Only the genus Prevotella 1 was differentially abundant between HFE and LFE cohorts. Although no major compositional shifts of bacterial populations were identified amongst the feed efficient cohorts (FDR > 0.05), correlation analysis identified putative drivers of feed efficiency with Ruminococcaceae UCG-014 (liquid, rho = −0.53; solid, rho = −0.56) and Olsenella (solid, rho = −0.40) exhibiting significant negative association with FCR (P < 0.05). Bifidobacterium and Megasphaera showed significant positive correlations with ADG. Major cellulolytic bacteria Fibrobacter (liquid, rho = 0.43) and Ruminococcus 1 (liquid, rho = 0.41; solid, rho = 41) correlated positively with FCR (P < 0.05). Our study provides evidence that feed efficiency in sheep is likely influenced by compositional changes to the archaeal community, and abundance changes of specific bacteria, rather than major overall shifts within the rumen microbiome.